The Dark Side of Leadership: A Three-Level Investigation of the Cascading Effect of Abusive Supervision on Employee Creativity - Liu, Dong; Liao, Hui; Loi, Raymond (Academy of Management Journal, 2012)
This research sheds light on the role of the dark side of leadership in employee creativity by examining how and when department leader abusive supervision may flow down organizational levels to undermine team member creativity. Analyses of multiphase, multisource, and multilevel data show that team leader abusive supervision mediates the negative relationship between department leader abusive supervision and team member creativity. Team leaders' and members' attributions for the motives behind their own supervisors' abusive supervision, which we classify as performance-promotion and injury-initiation motives, determine the extent to which team leader abusive supervision accounts for the effect of department leader abusive supervision on team member creativity.